Magnesium Removal from an Aluminum A-332 Molten Alloy Using Enriched Zeolite with Nanoparticles of SiO2 - Muñoz Arroyo, R.; Hernández García, H. M.; Escobedo Bocardo, J. C.; Granda Gutiérrez, E. E.; Acevedo Dávila, Jorge Leobardo; Aguilar Martínez, Josué Amilcar; Garza Gómez, A. (Hindawi Publishing Corporation, 2014)
In order to improve the Mg removal from an A-380 molten alloy, mixtures of zeolite and SiO2 nanoparticles (SiO2(NPs)) were tested. Zeolite was enriched with 2.5, 5, 7.5, 10, or 12.5 wt-% of amorphous SiO2(NPs). The SiO2(NPs) and zeolite were mixed for 30 min in ethanol for each experiment and then dried in a furnace at 80°C for 12 h. The enriched zeolites were analyzed by scanning electron microscopy, transmission electron microscopy, and N2 gas adsorption analysis. The Mg removal was carried out injecting each mixture into the molten aluminum alloy at 750°C using argon. The Mg content of the molten alloy was measured after different periods of the injection time. Zeolites enriched with 2.5 and 5 wt-% of SiO2(NPs) were demonstrated to be the better mixtures, removing Mg from an initial content of 1.6 to a final content of 0.0002 and 0.0101 wt-%, respectively, in 45 min of injection.